The Influence of Parental Acceptance Rejection and Mother Child Attachment to Discipline among Preschool Age Children - Neneng Dessy Rahayu; Dwi - Hastuti (Journal of Child Development Studies, 2017)
This study aimed to analyze influence of parental acceptance rejection, mother child’s attachment to discipline among preschool age children. The sample criteria of this study are mother as primary caregiver and has child who study in PAUD Mawar and Nurul Fajria, Ciasmara Village, Pamijahan district, Bogor Regency. This study involved 36 families with preschool children, which are chosen purposively. The data were analyzed using chi-square test, Pearson correlation and multiple linear regression. Parental acceptance and discipline classified to low category, the average of mother child’s attachment is classified good. There was a significant positive correlation between mother child attachment with parental acceptance and discipline of children. The result of multiple linear regression showed that there is negative influence between length of mother’s education to child’s discipline, meanwhile there is significant positive influence between income percapita and mother child’s attachment to discipline children.